2021
DOI: 10.1108/jed-02-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

Regional economic integration, natural resources and foreign direct investment in SADC

Abstract: PurposeThis paper aims to examine the role of economic integration and natural resources and foreign direct investment (FDI) complementarity in explaining economic growth in the Southern African Development Community (SADC).Design/methodology/approachThe study employed the ordinary least square-random effects and the generalized two-stage least square instrumental variables (IV) regression to examine the relationship between the variables.FindingsThe authors find that regional economic integration and natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…De Gregorio (2003) found that countries with high levels of human capital and extensive natural resource bases, such as Scandinavian countries, can leverage their natural resources for economic growth without negative consequences. Industrialized countries have also been able to protect their natural resources and reduce their reliance on raw materials through technological advancement (Redmond & Nasir, 2020;Haseeb et al, 2021;Adika, 2022). Natural resource abundance tends to increase per capita incomes in countries with less government intervention, more sound money, better property rights protection, less openness to international markets, or less government corruption (Kim & Lin, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…De Gregorio (2003) found that countries with high levels of human capital and extensive natural resource bases, such as Scandinavian countries, can leverage their natural resources for economic growth without negative consequences. Industrialized countries have also been able to protect their natural resources and reduce their reliance on raw materials through technological advancement (Redmond & Nasir, 2020;Haseeb et al, 2021;Adika, 2022). Natural resource abundance tends to increase per capita incomes in countries with less government intervention, more sound money, better property rights protection, less openness to international markets, or less government corruption (Kim & Lin, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A further increase in the size of the natural resource sector leads to a negative effect of FDI on economic growth. Adika (2022) investigated the complementary roles of economic integration, natural resources, and FDI in explaining economic growth in the Southern African Development Community (SADC) region. The study used OLS and IV estimators to control for potential endogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…They discussed whether the regional trading arrangements conferred any real benefits on the stakeholders, and suggested alternative approaches that may increase the benefits for Uganda from trade liberalization within the customs union. Adika (2021), in his study of regional integration and international trade in SADC, concluded that trade in the region can contribute substantially to provide improved economic growth. Besides, he noted that there was a considerable scope for greater intra-regional trade and growth in international businesses if key policies to enhance regional economic integration were put in place.…”
Section: Has Regional Integration Achieved Its Role In Enhancing Inte...mentioning
confidence: 99%
“…Konstantinus et al (2019) urge improving the regional freight transport inflow system to make the SADC more competitive. Adika's (2022) study implies that the SADC needs international cooperation and deeper regional trade integration to become more attractive. Ngeendepi and Phiri (2021) investigated the SADC region's vulnerability by focussing on the crowding-in/out effect of FDI and government expenditure on the SADC members' private domestic investment.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows that the SADC countries are located in the southern end of Africa, including four Indian Ocean islands. Studies such as Konstantinus et al (2019), Chamisa (2020), Ngeendepi and Phiri (2021), Pretorius et al (2021), andAdika (2022) all emphasise to some extent the SADC region's vulnerability as an investment destination. Some selected indicators are provided in Table 1 below to gain some perspective on the relativity within the SADC region.…”
mentioning
confidence: 99%